A review of the use of adapalene for the treatment of acne vulgaris - Piskin, Suleyman (Dove Medical Press, 2007)
Acne is a disease of the pilosebaceous unit with involving abnormalities in sebum production, microbial flora changes, abnormal keratinization, and inflammation. There are several therapeutic options like topical and systemic retinoids, antibiotics, and systemic hormonal drugs. The topical retinoids a play very important role in the treatment of acne vulgaris. However, their use is limited due to skin irritation. A new generation product, adapalene is a good choice in the treatment of acne vulgaris with less side effects and high efficacy confirmed by numerous clinical studies.